The growth and yield responses of two bean cultivars to organic and inorganic nitrogen sources - DARWIN H. PANGARIBUAN; ERMAWATI ERMAWATI; NI MADE WIDI SURYANI; WAHYU SARA MARIA (Society for Indonesian Biodiversity, 2022)
Abstract. Pangaribuan DH, Ermawati, Suryani NMW, Maria WS. 2022. The growth and yield responses of two bean cultivars to organic and inorganic nitrogen sources. Biodiversitas 23: 1677-1682.The productivity of beans is increased by selecting the best cultivar and applying fertilizers according to the needs of the plant. In addition,the application of high-yielding cultivar and N fertilizers with the right dosage could be used to increase the yield. Therefore, the objective of thisstudy is to determine the effect of nitrogensources on the growth and yieldof two bean cultivars. A5×2 factorial treatment was usedin a randomized block design with three replications. The first factor is the Perkasa and Lebat-3 cultivar, the second is organic and inorganic nitrogen fertilizer, namely control, urea 100kgha-1, as well as 10, 20, and 30% concentrationsof liquid organic fertilizer from leucaena leaves. The results showed that the use of liquid organic fertilizers derived from leucaena could be used as an alternative to nitrogenfertilization. Furthermore,the 20% concentrationtreatment producedthe highest number of trifoliate leaves (8.81 leaves) and dry weight (4.52 g). Based on the results,the use of 20% liquid organic fertilizer withPerkasa cultivar showed the best effect on the number of pods per plant (13.38),and yield(846.67 kg ha-1). The technology of liquid organic fertilizers from leucaena leaves could be recommended for bean organic production.